Comparison between single port videolaparoscopy and miniceliotomy with snock hook ovariohysterectomy techniques in bitches - Coutinho, Alexandre José [UNESP]; Gasser, Beatriz [UNESP]; Rodriguez, Mariana Garcia Kako [UNESP]; Uscategui, Ricardo Andres Ramirez [UNESP]; Santos, Victor José Correia [UNESP]; Tiosso, Caio de Faria [UNESP]; Barros, Felipe Farias Pereira da Câmara; Toniollo, Gilson Hélio [UNESP] (FapUNIFESP (SciELO), 2018)
In order to use and study minimally invasive techniques to reduce side effects of ovarian-hysterectomy (OHE) in bitches, the aim of this study was to compare time, surgical complications, pain and postoperative inflammatory response, caused by single port videolaparoscopic OHE and traditional miniceliotomy with snook hook. Twenty-four healthy bitches were randomly divided in two groups: videolaparoscopy (Video) and miniceliotomy (MiniLap). Surgical time and complications, pain, need for analgesic rescue, C-reactive protein concentration, glycaemia and voluntary food ingestion were evaluated during 24 hours following the procedure and compared statistically. Surgical time (38±7min), surgical complications (17%), postoperative pain intensity, need for analgesic rescue and C-reactive protein concentration were similar between groups (P>0.05). Glycaemia was lower in Video group (P=0.03), animals fed faster and in greater proportion (P=0.02). Thus, it is concluded that both OHE techniques result in similar complications, surgical time and inflammatory response; however, animals on Video group fed more readily and presented lower glycaemia, which point to lower stress levels. These findings validated the indication of this technique.
Comparação das técnicas videolaparoscópica com único portal e miniceliotomia com gancho de snook para ovário-histerectomia em cadelas
Keywords: C-reactive protein; Glycaemia; Postoperative pain; Surgical complications; Videosurgery